A conceptual model of feedback mechanisms in adjusted affordances – Insights from usage of a mental mobile health application. (April 2023) - Meske, Christian; Amojo, Ireti; Thapa, Devinder
Abstract: Affordance theory provides one of the most prominent lenses through which the socio-technical aspects of a system's use can be investigated and understood. In this context, the literature has proposed that perceived and actualized affordances may be adjusted over time. Yet, how the adjustment of affordances occurs has not been explained in detail. Thus, in this article, we develop a conceptual model of feedback mechanisms that includes a more explicit description of how affordances are perceived by users, whether actualized and adjusted. With the model, we introduce the central concept of a generative base, out of which affordance perceptions emerge and which can be updated through affordance actualizations. With this base, we integrate mental model (MM) theory to explain better the differing perceptions before and after actor–artifact interactions. Our conceptual model is illustrated and specified using an empirical case of the mental mobile health (mHealth) app "Between The Lines" in Germany. In this study, we conducted 40 interviews in two rounds with 20 teenage app users. Our results show that the users' perceptions of mHealth affordances become adjusted and hence change over time due to experiencing the actualization process, which may lead to an update of the generative base, including the user's MM. Highlights: Affordance Theory is one of the most prominent lenses to investigate IT use. We clarify how the perception of technological affordances is adjusted over time. A conceptual model of feedback mechanisms in adjusted affordances is introduced. The conceptual model is illustrated by insights from usage of a mental mHealth app. Results highlight the role of updated mental models for adjusted affordance perception.